2018
DOI: 10.1039/c8ra05847d
|View full text |Cite
|
Sign up to set email alerts
|

Detection of newly emerging psychoactive substances using Raman spectroscopy and chemometrics

Abstract: A novel approach for the identification of New Psychoactive Substances (NPS) by means of Raman spectroscopy coupled with Principal Components Analysis (PCA) employing the largest dataset of NPS reference materials to date is reported here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…This approach should be adopted routinely (Hikin et al, 2018), and especially in cases of death from uncertain or questionable causes (Lucyk and Nelson, 2017; Prekupec et al, 2017; Drummer, 2018). New approaches for the detection of potential unknown psychoactive substances, e.g., in the Emergency Departments, need to be developed, in order to identify and classify compounds that are new to the market and absent from existing chemical libraries (Assi et al, 2015; Guirguis et al, 2017; Calvo-Castro et al, 2018; Food and Drug Administration [FDA], 2018; News Release, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This approach should be adopted routinely (Hikin et al, 2018), and especially in cases of death from uncertain or questionable causes (Lucyk and Nelson, 2017; Prekupec et al, 2017; Drummer, 2018). New approaches for the detection of potential unknown psychoactive substances, e.g., in the Emergency Departments, need to be developed, in order to identify and classify compounds that are new to the market and absent from existing chemical libraries (Assi et al, 2015; Guirguis et al, 2017; Calvo-Castro et al, 2018; Food and Drug Administration [FDA], 2018; News Release, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Spectral preprocessing is a common strategy to extract useful information from the raw spectral data and remove nonselective systematic and random signal fluctuations. 24,25,37 Figure 2 shows the (a) raw spectral data, (b) data after SNV preprocessing, (c) subsequent smoothing, and (d) a 1,560-to 1,756-cm −1 selection with baseline correction for both cocaine HCl and cocaine base. Spectra of the cutting agents levamisole, paracetamol, and procaine are shown in the same plots to demonstrate the spectral selectivity.…”
Section: Spectral Selectivitymentioning
confidence: 99%
“…The spectral selectivity of Raman spectroscopy for pure drug substance detection and classification was demonstrated by Calvo Castro et al, who analyzed a large set of 478 NPS and visualized several group-specific features using PCA. 25 Supervised chemometric approaches were applied for classification or quantification issues within and outside the forensic field. Jiménez Carvalo et al 26 applied partial least squares (PLS) discriminant analysis (PLS-DA) and regression (PLS-R) on Raman spectra for olive oil classification and quantification.…”
mentioning
confidence: 99%
“…For an extensive review on chemometric applications in forensics, refer to Silva et al [ 12 ] and Sena et al [ 18 ] Recently, three studies reported the use of Raman spectroscopy and Principal Component Analysis (PCA) to evaluate differences and similarities among NPS samples and improve chemical characterization. [ 15,19,20 ] In another study, [ 21 ] Partial Least Squares Discriminant Analysis (PLS‐DA) was employed to classify NPS infrared spectral data. Although these studies showed the great potential of the spectroscopic techniques to analyze a diversity of NPS samples, the chemometric models presented were not robust for field applications, and their performance was negatively influenced by the diversity of chemical components usually found in street NPS samples.…”
Section: Introductionmentioning
confidence: 99%